Emotional Tears Communicate Sadness but Not Excessive Emotions Without Other Contextual Knowledge - Ito, Kenichi; Ong, Chew Wei; Kitada, Ryo (Frontiers in Psychology, 2019)
Contexts of face perception are diverse. They range from the social environment to body postures, from the expresser’s gaze direction to the tone of voice. In extending the research on contexts of face perception, we investigated people’s perception of tears on a face. The act of shedding tears is often perceived as an expression of sad feelings aroused by experiencing loss, disappointment, or helplessness. Alternatively, tears may also represent the excessive intensity of any emotion, such as extreme fear during an unexpected encounter with a giant bear and extreme happiness when you win a competition. Investigating these competing interpretations of tears, we found that the addition of tears to different facial expressions made the expressions conceptually closer to sad expressions. In particular, the results of the similarity analysis showed that, after the addition of tears, patterns of ratings for anger, fear, disgust, and neutral facial expressions became more similar to those for sadness expressions. The effect of tears on the ratings of basic emotions and their patterns in facial expressions are discussed.